The Role of the Characteristics of Urban Furniture and Equipment on the Quality of the Public Space of the Pedestrian Zone - Brkljač Dijana; Milinković Aleksandra; Škorić Stefan; Šanjević Ivana (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Public spaces are complex structures that contain numerous elements formed by various influential forces such as social relations, spatial elements, contemporary tendencies of city life and many others. The quality of the city's public space determines the frequency of its use, the concentration of content and the intensity of the experience that a place will have on its users. The paper describes the results of research that indicate the influence of the characteristics of urban furniture and equipment as architectural and urban planning elements on the quality of public spaces in the city center. The systematization of the results of the comparative analysis of theoretical positions helped to form three groups of characteristics of architectural-urban elements: spatial, physicomorphological and functional. Through the conducted survey, the opinion of users of the pedestrian zone of Novi Sad was investigated regarding the importance of the researched group of public space elements on their experience of the place.